The Effect of Sustainability Report Disclosure and Innovations on Earnings Informativeness with Environmental Performance as a Moderating Variable - Dhyanasaridewi, I Gusti Ayu Diah; Murwaningsari, Etty (Journal of Accounting, Business and Finance Research, 2021)
As climate change worsens, businesses must pay more attention to how their activities affect the environment. The aim of this current research is to analyze at the influence of environmental performance in moderating the relationship between sustainability reporting disclosure and earnings informativeness. A purposive sampling method was used to identify forty-two companies in the manufacturing and mining sectors listed on the Indonesia Stock Exchange (IDX) that follow the Program for the Assessment of Company Performance Ratings in Environmental Management (PROPER) consistently and published audited annual reports from 2017–2019. The absolute difference method was used to test the effect of the moderating variable, and SPSS 27 was used as a statistic analytical tool to analyze the hypothesis. The empirical test results indicate that environmental performance could weaken the effect of sustainability report disclosure on the informativeness of earnings, and it could also strengthen the influence of corporate innovation on earnings informativeness. On the other hand, environmental performance doesn’t have a significant direct effect on the informativeness of earnings.